Application of The Problem-Based Learning (PBL) Model Using The Education for Sustainable Development (ESD) Approach to Students' Critical Thinking Ability in Global Warming Material - Mochamad Raihan Ahnaf Rizqulloh; Heni Rusnayati; Agus Danawan (Jurnal Ilmiah Pendidikan Fisika, 2024)
The rapid development of the Industrial Revolution 4.0 era requires humans to withstand rapid changes. Mastery of 21st-century skills and sustainability awareness becomes crucial as society in this era is required to sustain Natural Resources (NR) and develop Human Resources (HR) preparedness to adapt. Critical thinking is one of the competencies that students must possess in the 21st century and is also a key competency in ESD that can help students realize the concept of sustainability awareness in the Industrial Revolution 4.0 era. A learning model that can develop students' critical thinking skills is the PBL model because thinking and problem-solving skills can be developed when students do it themselves, explore, and transfer the complexity of existing knowledge. Therefore, this study aims to determine the application of the PBL model with an ESD approach to students' critical thinking skills on global warming material. This research uses the quantitative method of pre-experimental designs with the One Group Pre-test-posttest design. The subjects of this study were 38 students at a public high school in Bandung. The sample was taken using the convenience sampling method on 11th-grade science students in the even semester of the 2022/2023 academic year. The instruments used in this study were a critical thinking skills test and a sustainability awareness questionnaire using the Guttman scale. The data obtained were processed using the Normalized Gain (N-Gain) test for critical thinking skills and the response percentage for the sustainability awareness questionnaire. The results showed increased students' critical thinking skills N-Gain of 0.524 in the medium category. Meanwhile, the sustainability awareness questionnaire profile after learning activities showed a total percentage of 73.94% in the high category.